Densidade de madeira e alometria de árvores em florestas do arco do desmatamento: implicações para biomassa e emissão de carbono a partir de mudanças de uso da terra na Amazônia brasileira - Nogueira, Euler Melo (Instituto Nacional de Pesquisas da Amazônia – INPA, 2008)
Uncertainties in biomass estimates are the main source of uncertainty in estimates of greenhouse-gas emissions in Amazonia. The results presented in this study reduce the uncertainties in estimates of above-ground biomass, particularly in the southern and southwestern portions of the Brazilian Amazon (SSWA), which are in the arc of deforestation. In Chapter I new data on wood density obtained in the forests of the SSWA area (403 trees identified to species or genus) are combined with the inventories of wood volume produced by Projeto RadamBrasil (1973-1983). The area of each vegetation unit, defined as the intersection among forest types and the boundaries of the nine states in Brazilian Amazonia, was used to calculate a mean wood density of 0.583 g.cm-3 for the SSWA as a whole. This average is 13.6% lower than the value used for this area in previous estimates. An average of 0.642 g.cm-3 was obtained for the Brazilian Amazon as a whole, starting from the new estimates for the forests of the SSWA together with estimates for the other areas of Amazonia, corrected for radial variation (-5.3%). The new density average is 7% lower than the average previously used for the Brazilian Amazon (0.69 g.cm-3). The impact on estimates of biomass and carbon emission is substantial because the reduction is largest in the forest types experiencing the most rapid deforestation. For 1990, with 13.8 × 103 km2 of deforestation, the estimated emission for the Brazilian Amazon would be reduced by 23.4-24.4 × 106 CO2-equivalent Mg C/year (for high and low trace-gas scenarios), or 9.4- 9.5% of the gross emission and 10.7% of the net committed emission, both excluding the soil. In Chapter II linear relationships were appraised that describe the radial variation of density for trees in dense forest in the central Amazon (CA) and new relationships are developed for trees in open forest in the southern Amazon (SA). The linear relationship described in CA for the variation of density along the bole is similar for trees in SA (p = 0.144). It is also demonstrated that the trees in the southern Amazon have significantly higher humidity content in their boles (0.416 ± 0.068 SD; n = 223) than do trees in CA (0.38; n = 50). Moisture content of the bole had a strong inverse relationship with basic wood density and explains the lower moisture content in the trees in CA relative to SA. In Chapter III CA trees are shown to be taller for any given diameter than they are in bamboo-dominated dense forests, bamboo-free dense forests and open forests in the southwestern Amazon (SW), as well as in the open forests of the southern Amazon (SA). The impact on biomass estimates is - 11.0%, -6.2% and -3.6%, respectively. This suggests that the estimate of the Brazilian National Communication to the United Nations Framework Convention on Climate Change requires revision. The relationships observed between diameter and height were inconsistent with the assumptions of metabolic ecological theory and the findings reinforce the argument that the scalar allometric exponent varies among forests growing on different substrata or with different levels of natural disturbance. In Chapter IV new allometric equations for biomass are derived starting from trees weighed directly in SA and from equations for estimates of volume of the bole in CA and in SA. These equations were used to improve the biomass model historically applied in Amazonia, which is based on large-scale inventories of wood volume. A new biomass estimate is produced for the Brazilian Amazon incorporating new values of wood density, corrections for uncertainties in estimates of wood volume and new values for factors used to add the volume of the boles of small trees and the biomass of the crowns. Considering all adjustments the biomass map indicates average biomass of 125.4 Pg (=1015 g) dry weight (above-ground + below-ground) for originally forested areas in the Brazilian Legal Amazon as a whole (104.2 Pg for above-ground only) at the time of the RadamBrasil inventories, which was before intensive deforestation had occurred in the region. If areas deforested through 2006 are eliminated, excluding agriculture, pasture and secondary forest vegetation, the estimation of dry biomass storage was reduced to 113.3 and 94.2 Pg (aboveground + below-ground and only above ground).
Keywords: Aquecimento global; Densidade da madeira; Alometria